Effect of green tea on serum cholesterol level in cholesterol fed rabbits (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Since the development of atherosclerosis involves dyslipidemia, we postulated that green tea may exert lowering of serum cholesterol levels. Objectives: To investigate the effects of green tea on serum cholesterol level. Methods: Total 45 rabbits (15 were fed on 1% cholesterol and green tea for 16 weeks, another 15 were fed on 1% cholesterol and plain water for 16 weeks, last batch of 15 rabbits received normal rabbit diet for 16 weeks) in the department of Cardiac Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from April 2011 to September 2012.They were evaluated for lipid profile and presence of atherosclerosis. Results: The mean total cholesterol in cholesterol fed rabbits with green tea after 16 weeks was 21.06 ± 5.55, LDL-C was 20.80 ± 6.16, Serum TG was 153.67 ± 33.59, HDL-C neither increased nor decreased. The mean total cholesterol in cholesterol fed rabbits with plain water after 16 weeks was 27 .53 ± 5.15, LDL-C was 32.40 ± 8.24 and TG was 290.13 ± 44.31, no effect were seen on HDL-C. These rabbits were fed on green tea for 8 weeks, cholesterol levels returned to levels at commencement of experiment. Rabbits fed on normal rabbit diet for 16 weeks had TC l9.20 ± 4.85, LDL-C was 19.20 ± 2.04 and TG was 155.06 ± 32.03 mg/dl. HDL-C remained in normal range. But there was no atheroschlerotic change in any group. Conclusion: Green tea significantly reduces serum cholesterol levels in cholesterol fed rabbits. There was no effect of green tea on HDL-C in any group.